2017
DOI: 10.1590/1806-9282.63.12.1076
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a standardized out-of-hospital management method for Parkinson dysphagia

Abstract: Objective: Our objective is to explore the effectiveness and feasibility of establishing a swallowing management clinic to implement out-of-hospital management for Parkinson disease (PD) patients with dysphagia. Method: Two-hundred seventeen (217) voluntary PD patients with dysphagia in a PD outpatient clinic were divided into a control group with 100 people, and an experimental group with 117 people. The control group was given dysphagia rehabilitation guidance. The experimental group was presented with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…After removal of duplicates, a total of 4326 records were screened, of which 150 full-text articles were considered potentially eligible for inclusion. Following detailed screening 14 articles [18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included in the systematic review. The majority of the excluded articles did not relate to oral nutrition or the study design did not include a control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removal of duplicates, a total of 4326 records were screened, of which 150 full-text articles were considered potentially eligible for inclusion. Following detailed screening 14 articles [18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included in the systematic review. The majority of the excluded articles did not relate to oral nutrition or the study design did not include a control group.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 14 included studies are reported in Tables 2 and 3 as well as Supplementary Table 1. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] All included studies were intervention studies with a control group reporting on interventions used to promote oral nutritional behaviours in participants with NDMS. Eight studies reported on interventions used to assist with swallowing difficulties 19 20 22 23 25 26 29 30 and six studies 18 21 24 27 28 31 reported on interventions targeting dietary content.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations